Turning a blind eye: How lack of communication with ER nurses nearly cost a patient permanent vision loss - Kenneth Royal; April Kedrowicz (The Beryl Institute, 2017)
This narrative presents a case in which a patient was treated for conjunctivitis, but a breakdown in several layers of communication (between the hospital and the patient, and between hospital personnel) resulted in multiple medical errors that nearly costs the patient permanent vision loss. This real-life case underscores how simple communication errors may lead to life-altering consequences. Recommendations for improving communication to ensure similar errors do not happen to others are provided.